2017
DOI: 10.1515/pthp-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Physico-Chemical Stability of Dexamethasone Oral Suspension

Abstract: AbstractBackgroundDexamethasone is commonly used to treat a wide variety of diseases including oncological disorders. The aim of this study was to propose a liquid formulation of dexamethasone. Therefore we have developed and assessed the stability of a 5 mg/mL dexamethasone oral suspension.MethodsA stability-indicating analytical method, using HPLC-UV, was developed and fully vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Regardless of the type of storage conditions, the proportion of the initial concentration of dexamethasone, hydrochlorothiazide, phenytoin, or spironolactone remaining was within the limit set by the U.S. Pharmacopeia [26], meaning that the oral suspensions of each drug compounded using Syrspend® SF PH4 Dry were stable up to 60 days both at room temperature or under refrigeration. This result is similar to or greater than the stability period reported by others [9,10,11,12,13,14,15]. The physicochemical stability of the four oral liquid dosage forms was investigated for a period of 60 days since the microbiological stability of suspensions compounded using Syrspend® SF PH4 Dry has been demonstrated by the manufacturer over the same period [30].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Regardless of the type of storage conditions, the proportion of the initial concentration of dexamethasone, hydrochlorothiazide, phenytoin, or spironolactone remaining was within the limit set by the U.S. Pharmacopeia [26], meaning that the oral suspensions of each drug compounded using Syrspend® SF PH4 Dry were stable up to 60 days both at room temperature or under refrigeration. This result is similar to or greater than the stability period reported by others [9,10,11,12,13,14,15]. The physicochemical stability of the four oral liquid dosage forms was investigated for a period of 60 days since the microbiological stability of suspensions compounded using Syrspend® SF PH4 Dry has been demonstrated by the manufacturer over the same period [30].…”
Section: Discussionsupporting
confidence: 77%
“…To enable the appropriate volume of administration (preferably ≤1 mL for a newborn), according to the dose required in their therapeutic uses [6,8,28], we chose to prepare oral liquid dosage forms at a target concentration of 5 mg/mL for spironolactone, dexamethasone, and phenytoin and 2 mg/mL for hydrochlorothiazide. According to the literature, other authors have reported similar concentrations for oral liquid compounded preparations of the same APIs [10,13,15]. Some authors have proposed oral liquid dosage forms with lower strengths due to different therapeutic uses [12,14] or higher strengths since they were used in older children [9,11].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The offered analytical method has been established using a high performance liquid chromatography (HPLC) technique coupled with ultraviolet (UV) detection and is revealed as fast and cost-effective in routine pharmaceutical analyses. Although evidence has been presented for the feasibility of DX and MEL quantification, several methods lacking simultaneous determination of the two mentioned compounds, or with longer retention times, have been described [28][29][30]. To the authors' knowledge, there is no reversed phase HPLC-UV validated method in the literature for the quantification of DX and MEL simultaneously with a short analysis time that involves a reduction in solvent consumption.…”
Section: Introductionmentioning
confidence: 99%